The effects of sex, gender role, and personality traits on leader emergence - Does culture make a difference? - (:unkn) unknown (SAGE PUBLICATIONS INC, 2008)
This study investigated the effects of sex, gender roles, and personality (self-monitoring, self-efficacy, and dominance) on leader emergence in Turkish university students. Two hundred and nineteen business students filled in personality and gender role inventories, and 60 of them were selected by personality and sex to join in a 4-person leaderless group discussion involving a gender-neutral task. At the completion of the sessions, they evaluated each other on leadership perception and preferences. Results showed that the only personality trait predicting leader emergence in Turkish students was self-monitoring. Differing from studies conducted in Western cultures, dominance, self-efficacy, sex, and gender role orientation were not found to predict emergent group leaders. This difference is explained within the context of Turkey's feminine and collectivist cultural characteristics. The study supports the idea that North American research findings on group leadership perceptions should be tested in other cultures. This issue is especially important for global organizations functioning worldwide.
Keywords: leader emergence; sex; gender role; dominance; self-efficacy; self-monitoring; culture; ROLE CONGRUITY THEORY; SELF-EFFICACY SCALE; MODERATING ROLE; PROJECT GLOBE; PERCEPTIONS; BEHAVIOR; PERFORMANCE; CONSTRUCT; CATEGORIZATION; METAANALYSIS